Lung Vascular Targeting Using Antibody to Aminopeptidase P: CT-SPECT Imaging, Biodistribution and Pharmacokinetic Analysis - Chrastina, A. (S. Karger AG, 2010)
BACKGROUND/AIMS: Aminopeptidase P (APP) is specifically enriched in caveolae on the luminal surface of pulmonary vascular endothelium. APP antibodies bind lung endothelium in vivo and are rapidly and actively pumped across the endothelium into lung tissue. Here we characterize the immunotargeting properties and pharmacokinetics of the APP-specific recombinant antibody 833c. METHODS: We used in situ binding, biodistribution analysis and in vivo imaging to assess the lung targeting of 833c. RESULTS: More than 80% of 833c bound during the first pass through isolated perfused lungs. Dynamic SPECT acquisition showed that 833c rapidly and specifically targeted the lungs in vivo, reaching maximum levels within 2 min after intravenous injection. CT-SPECT imaging revealed specific targeting of 833c to the thoracic cavity and co-localization with a lung perfusion marker, Tc99m-labeled macroaggregated albumin. Biodistribution analysis confirmed lung-specific uptake of 833c which declined by first-order kinetics (t(½) = 110 h) with significant levels of 833c still present 30 days after injection. CONCLUSION: These data show that APP expressed in endothelial caveolae appears to be readily accessible to circulating antibody rather specifically in lung. Targeting lung-specific caveolar APP provides an extraordinarily rapid and specific means to target pulmonary vasculature and potentially deliver therapeutic agents into the lung tissue.